2012
DOI: 10.1089/lap.2010.0467
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Maze of Minimally Invasive Surgery Simulators

Abstract: Background: Conforming to, among other considerations, legal and ethical concerns for patient safety, there is an increasing demand to assess a surgeon's skills prior to performance in the operating room in pursuit of higherquality treatment. Training in minimally invasive surgery (MIS) must therefore be intensified, including team training. New methods to train and assess minimally invasive surgical skills are gaining interest. The goal of this review is to provide instructors with an overview of available MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…2 To ensure the validity of a simulation, a number of different techniques have been described [3][4][5] : (1) Construct validity tests to what extent the skill we are seeking to measure, is actually being measured. The use of simulation in surgical selection is also practiced; however, it is important that these tests are valid if they are to be adopted into an equitable system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 To ensure the validity of a simulation, a number of different techniques have been described [3][4][5] : (1) Construct validity tests to what extent the skill we are seeking to measure, is actually being measured. The use of simulation in surgical selection is also practiced; however, it is important that these tests are valid if they are to be adopted into an equitable system.…”
mentioning
confidence: 99%
“…3,[6][7][8][9][10][11][12][13][14] On the basis of these measures of concurrent and construct validity, we aim to evaluate the appropriateness of high-fidelity and low-fidelity tasks in surgical selection. Two popular systems that have been well validated include the low-fidelity Fundamentals of Laparoscopic Surgery box trainer (FLS) and the high fidelity, Lapsim, virtual reality trainer.…”
mentioning
confidence: 99%
“…There is a wide variety of simulators on the marked, ranging from virtual reality (VR) simulators to box-trainers, several of which have already been validated [14]. VR simulators are based on computer-generated environments and can simulate both basic tasks and full procedures.…”
Section: Laparoscopic Simulation Training Has Been Shown To Improve Technical Skills Compared To Nomentioning
confidence: 99%
“…Furthermore, VR and AR simulators do not provide tactile (haptic) feedback. Box trainers do preserve a realistic setting including haptic feedback and augmented depth perception [8] but would lack objective assessment methods and a low fidelity to actual laparoscopic procedures [9].…”
Section: Introductionmentioning
confidence: 99%
“…Various validation studies have demonstrated objective classification of MIS skill using laparoscopic simulators, although there is little evidence that these systems can assess residents' individual laparoscopic performance correctly [8].…”
Section: Introductionmentioning
confidence: 99%